Atypical Manifestations of Cowden Syndrome in Pediatric Patients - Ekaterina Zelenova; Tatiana Belysheva; Elena Sharapova; Irina Barinova; Alexandra Fedorova; Vera Semenova; Yana Vishnevskaya; Irina Kletskaya; Anna Mitrofanova; Denis Sofronov; Ivan Karasev; Denis Romanov; et al. (Diagnostics)
Background/Objectives: Cowden syndrome (or PTEN hamartoma tumor syndrome) (CS/PHTS) belongs to a group of inherited disorders associated with the development of multiple hamartomas. The clinical presentation of patients may include dysmorphic facial features, macrocephaly, developmental delay, and multiple benign and malignant tumors of various localizations. At the same time, only thyroid cancer is thought to have an increased risk in childhood. Skin lesions in CS/PHTS occur in 90–100% of patients and include multiple tricholemmoma, papilloma, acral keratosis, pigmentation changes, as well as rarer forms like vascular malformations, fibromas, neuromas, melanoma, and basal cell carcinoma. Methods: Next-generation sequencing and Sanger sequencing were used to search for PTEN genetic variants. A histological and immunohistochemical examination of tumor biopsies and skin lesions was performed. Results: A total of 13 patients from six families with CS/PHTS, including 10 children, were described. Seven pediatric patients belonged to families with paternal transmission of the PTEN pathogenic variants, while three others were de novo cases. Atypical manifestations in CS/PHTS were diffuse large B-cell lymphoma in one adult, a renal cell carcinoma, three germ cell tumors, and a linear epidermal nevus in pediatric patients. A literature review of the identified pathogenic variants in the PTEN gene was performed, assessing their clinical significance and analyzing the traditional and modified diagnostic criteria as applied to the pediatric population. Conclusions: Taking into account the low incidence of CS/PHTS, the data presented significantly expand our current understanding of this disease and guide physicians to consider a wider range of possible malignant neoplasms in pediatric patients with CS/PHTS.